Trade unionism in Australia : a history from flood to ebb tide - Bramble, Thomas (Cambridge University Press, 2008)
'Trade Unionism in Australia' charts the impact on unions of waves of economic restructuring, a succession of hostile governments and a wholesale shift in employer attitudes, as well as the failure of the unions' own efforts to boost membership and consolidate power.